Prophylaxis of febrile neutropenia with colony-stimulating factors: the first 25 years. (3rd March 2020) - Edelsberg, John; Weycker, Derek; Bensink, Mark; Bowers, Charles; Lyman, Gary H.
Abstract: Filgrastim prophylaxis, both primary and secondary, was rapidly incorporated into clinical practice in the 1990s. When pegfilgrastim became available in 2002, it quickly replaced filgrastim as the colony-stimulating factor (CSF) of choice for prophylaxis. Use of prophylaxis increased markedly in the first decade of this century and has stabilized during the present decade. Data concerning real-world CSF prophylactic practice patterns are limited but suggest that both primary and secondary prophylaxis are common, and that use is frequently inappropriate according to guidelines. The extent of inappropriate use is controversial, as are issues concerning the cost-effectiveness of prophylaxis versus no prophylaxis and the cost-effectiveness of primary prophylaxis versus secondary prophylaxis. Nevertheless, CSF prophylaxis is firmly established as a valuable adjunct to chemotherapy and will almost certainly continue to be widely used for the foreseeable future. In this article, we chronicle the use and impact of CSF prophylaxis in US patients receiving myelosuppressive chemotherapy for non-myeloid malignancies. We emphasize the interplay of expert opinion, clinical evidence, and economic factors in shaping the use of CSFs in clinical practice over time, and, with the recent introduction of new CSF agents and options, we aim to provide useful clinical and economic information for healthcare decision makers.